Pemahaman Mendalam Terhadap Nilai-Nilai Sila Persatuan Indonesia dalam Membangun Kesatuan dan Kesejahteraan Masyarakat di Lingkungan MMTC - Indah Puja Claudia Damanik; Damanik, Indah Puja Claudia; Simbolon, Boy Dippu Tua; Sitanggang, Agnes; Saragih, Rama Rizky Septienda; Boangmanalu, Vivin Silvia; Lumbanbatu, Lestari; Panggabean, Naulita; Nababan, Ramsul Yandi (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research aims to gain a deeper understanding of the values of the Indonesian Unity principle in fostering unity and prosperity within society, particularly in the MMTC Market environment. The research method used in this study is the qualitative descriptive method, which aims to understand a phenomenon. This study shows that when the community understands and applies the values of unity, they can create a more harmonious and prosperous environment. Despite facing some challenges, the collective efforts of the community and local leaders in promoting togetherness and mutual cooperation can create a harmonious and prosperous environment. Keywords: Pancasila principles, Unity, Togetherness, Community